‘Setting a good example for the ladies’: example setting as a technique of penal reform in specialized prostitution court - Singh, Rashmee (The British journal of criminology, 2018)
This article identifies and examines example setting as a penal technique of reform in one specialized prostitution court in Illinois. Drawing on court observation, I show how informal court practices materialize into visual and verbal narratives designed to valorize defendants who are benefitting from treatment. In exploring their effects, I argue that these stories are not just celebratory rituals. Rather, they are deployed to generate defendant comparisons and to rationalize the enhancement of punishment for those struggling to comply with program demands. The shared structural location of defendants, virtually all of whom are poor and racialized, facilitates this process through communicating the notion that individual will can ultimately overcome social disadvantage and criminalization. This analysis illuminates the role of unwritten and contingent court practices in the reform and responsibilization of criminalized women.